Attitudes, norms, and beliefs of pastoralists toward cheetahs in the Horn of Africa - Jones, Kelly W.; Evangelista, Paul; Durant, Sarah M.; Young, Nicholas E.; Tesfai, Redae T.; Ali, Abdullahi H.; Tricorache, Patricia; Mitchell, Nicholas; Maule, Tomas; Abdilahi, Mowlid Hassan; Edin, Aden Hussein; Edwin, Sangale; et al. (Frontiers in Conservation Science, 2025)
Free-ranging African cheetahs (Acinonyx jubatus) inhabit only 13% of their former range. A subspecies of particular conservation concern is the Northeastern African cheetah (A. j. soemmeringii), which has a tentative estimate of 500 mature individuals in the wild in the Horn of Africa. Human-cheetah interactions are common in this region, and anthropogenic drivers of cheetah loss include habitat loss, poaching, and the illegal trafficking of live cubs for the international wildlife trade. In this study we explore the human dimensions of human-cheetah interactions and the implications for cheetah conservation in the Horn of Africa. We conducted 222 social science surveys with pastoralists in the Somali Regional State of Ethiopia and Northeastern Kenya on levels of conflict with cheetahs, social norms toward killing and live capture of cheetahs, and attitudes toward cheetahs. We found high levels of livestock depredation, with more than 60% of respondents reporting a cheetah attack in the last year. More than 80% of survey respondents felt it was acceptable to kill a cheetah if it attacked livestock and that killing cheetahs was common in their area. About 30% of respondents reported it was acceptable to capture a live cheetah cub and that live capture occurred in their area. Both killing cheetahs and live capture of cubs were reported as motivated, in part, as a retaliatory response against cheetahs for livestock depredation. About 90% of respondents wanted to see the number of cheetahs decrease, and an ordinal logit regression showed that attitudes toward cheetahs were correlated with emotions, risk perceptions, beliefs about the efficacy of non-lethal mitigation, perceptions of benefits from cheetahs, and alternative income sources. The results from our study suggest that there is a critical need to co-develop cheetah coexistence strategies in the region that focus on reducing costs and increasing benefits of living with cheetahs; couple improvements in rangeland management with enhanced livelihood sustainability; and strengthen law enforcement.